Pengaruh Work-Life Balance, Budaya Organisasi, dan Reward Terhadap Disiplin Kerja - Fahma Putri Mahanani; Didik Subiyanto; Mohammad Ahyar Syafwan Lysander (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
In the era of digital transformation and intense global competition, employee discipline has become a major challenge for private organizations such as CV. Hivenley, where conflicts between work and personal life demands often decrease productivity and increase absenteeism. The purpose of this study is to examine the individual and combined impacts of work-life balance, organizational culture, and rewards on employee work discipline. The research method uses a quantitative approach with data from 81 CV. Hivenley employees collected through Google Forms, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to test the hypothesis. The findings indicate that work-life balance (β=0.360, p=0.001), organizational culture (β=0.225, p=0.025), and rewards (β=0.279, p=0.015) each have a significant positive effect on work discipline, with an explained variance of 49.6% (R²=0.496). The discussion reveals that the integration of these factors encourages the formation of a disciplined workforce, provides practical insights for managers to improve organizational performance, and enriches the human resource management literature with the emphasis on collaborative impact in the context of spiritually oriented companies, addressing the gaps of previous studies that often exclude these variables.